Perancangan bahasa sejarah aksara Jawi - Amat Juhari Moain; Dewan Bahasa dan Pustaka (Kuala Lumpur Dewan Bahasa dan Pustaka, 1996)
History of the Jawi alphabet & script and Islamic inscriptions in the Malay archipelago.
Includes bibliographical references (pages 169-176) and index.
In Malay.
AC-14594d donated by Roderick G. Orlina
Keywords: Jawi alphabet -- History; Islamic inscriptions -- Malay Archipelago -- History; Malay language -- Writing -- History